Prevención de Caídas: ¿Quién está a riesgo? - Sergio Romero; Linda B. Bobroff (EDIS)
Revised! FCS2227-Span, a 1-page handout by Sergio Romero and Linda B. Bobroff, is the Spanish language version of FCS2227/FY733: Fall Prevention: Who’s at Risk? It provides a short quiz to determine whether a person is at risk of falling. Published by the UF Department of Family Youth and Community Sciences, August 2010.